The meaning of the imago Dei (Gen 1 : 26-27) in Genesis 1-11 - Simango, Daniel ca. (Old Testament essays, 2012)
The purpose of this article is to define the image of God in Gen 1 : 26-27 in light of Gen 1-11. Does Gen 1-11 define or imply a definition of the image and likeness of God? The biblical-theological (or canonical-chronological) approach will be used which looks at how the idea of God-likeness (Gen 1 : 26-27) is seen in Gen 2-11. The article argues that the image of God is both moral and relational in perspective : it involves a moral likeness to God and a relationship between God and humans like that between parent and child. This is such an important topic because South Africa is experiencing a state of moral decay. The statement of human kind's creation in the "image of God" clearly constitutes an important and positive affirmation about human's original place in the created order. Various NT passages such as Col 3 : 10 and Eph 4 : 24 also emphasise this theme as the goal of the Gospel.